Memristor Based Filter Design and Implementation for ECG Signal - Sahin, Muhammet Emin; Karakaya, Barış; Güler, Hasan; Gülten, Arif; Hamamcı, Serdar Ethem (My University, 2020)
This paper presents memristor based filter implementation for a real time biomedical signal. The significance ofthis study is that the passive circuit element called memristor is completely linear in both experimental andsimulation studies at high frequencies and becomes indistinguishable from normal resistance. The variation of thememristance value gives possibility to tune the cut-off frequency of the filter circuit. For this purpose, memristorbased high-pass and low-pass filter circuits are constructed by simply replacing resistor with memristor emulatorcircuit in well-known R-C filter structures. The filter circuits are constituted on board and firstly sine wave isapplied as input signal. Then, Electrocardiographic (ECG) signal is applied as input for M-C filter circuits. Theresults are obtained and analyzed in real-time. In the implementation stage of study, LabVIEW platform and DAQcard are used to obtain real-time data. The results show that memristor can be used quite easily to sort outbiomedical signal processing applications and shows better performance.
Keywords: Mühendislik; Biyotıp; Mühendislik; Elektrik ve Elektronik